2021
DOI: 10.1071/rd21267
|View full text |Cite
|
Sign up to set email alerts
|

Female age and parity in horses: how and why does it matter?

Abstract: Although puberty can occur as early as 14–15months of age, depending on breed and use, the reproductive career of mares may continue to advanced ages. Once mares are used as broodmares, they will usually produce foals once a year until they become unfertile, and their productivity can be enhanced and/or prolonged through embryo technologies. There is a general consensus that old mares are less fertile, but maternal age and parity are confounding factors because nulliparous mares are usually younger and older m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 211 publications
0
9
0
Order By: Relevance
“…The increasing biopsy grade with age is consistent with various reports that biopsy grade, largely an index of endometrial fibrosis, was more common in older mares (Grüninger et al, 1998) and that pregnancy rate and pregnancy losses can be linked to age (Morris & Allen, 2002). A recent literature review reported that age critically affected cyclicity, folliculogenesis, oocyte and embryo quality as well as the presence of oviductal masses and uterine tract function (Derisoud et al, 2021). Increased parity and age was associated with a progressive decline in both endometrial quality and uterine clearance capacity (Derisoud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing biopsy grade with age is consistent with various reports that biopsy grade, largely an index of endometrial fibrosis, was more common in older mares (Grüninger et al, 1998) and that pregnancy rate and pregnancy losses can be linked to age (Morris & Allen, 2002). A recent literature review reported that age critically affected cyclicity, folliculogenesis, oocyte and embryo quality as well as the presence of oviductal masses and uterine tract function (Derisoud et al, 2021). Increased parity and age was associated with a progressive decline in both endometrial quality and uterine clearance capacity (Derisoud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review reported that age critically affected cyclicity, folliculogenesis, oocyte and embryo quality as well as the presence of oviductal masses and uterine tract function (Derisoud et al, 2021). Increased parity and age was associated with a progressive decline in both endometrial quality and uterine clearance capacity (Derisoud et al, 2021). Australian Thoroughbred mares at 20 years of age reportedly had <70% covering success between the years 2000 and 2017 (Todd et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The epitheliochorial placenta does not invade into the maternal endometrium to the same degree as a haemochorial placenta, therefore a far greater surface area of contact is required to support the developing foetus. The surface area of contact between the foetal allantochorion and maternal endometrium is estimated to be 38-50 m 2 in the TB mare, which is affected by numerous maternal factors reviewed by others (Derisoud et al 2021). As a result, primiparous mares produce lighter and smaller foals and placentae with a decrease foal to placenta surface ratio when compared with multiparous mares (Robles et al 2018).…”
Section: Placental Developmentmentioning
confidence: 99%
“…As in many other mammalian species studied to date (Quenby et al 2021), advancing maternal age is a well-known risk factor for early pregnancy loss in horses (Rose et al 2018;de Mestre et al 2019;Fawcett et al 2021). The pathologies of older mares are extensively reviewed by others (Derisoud et al 2021) and in brief include endometrial pathologies such angiosclerotic changes (Grüninger et al 1998) and lower quality oocytes and subsequently embryos (Rizzo et al 2019(Rizzo et al , 2020. In an attempt to differentiate between oocyte related issues and uterine related issues of older mares, morphologically normal embryos from cycling donor mares were transferred to either normal or sub-fertile mares (Ball et al 1987).…”
Section: Mare Level Risk Factorsmentioning
confidence: 99%
“…Indeed, in a recent epidemiological study considering the effect of parity only in mares older than 10 years, there is a cumulative negative effect of nulliparity and aging on the rates of pregnancy at 14 days postovulation (ED and PCP, personal communication). Maternal age have been shown to affect oocyte and embryo developmental capacities (for review [34]) as well as gene expression in Day 8 embryos [35]. At the opposite, only one study considered the effect of maternal parity on preimplantation embryo and showed alterations of the expression of genes related to embryo development and exchanges with the environment were observed [36].…”
Section: Introductionmentioning
confidence: 99%